Soft Systems Methodology as a Conceptual Framework for Vehicle Routing Problem: (Case Study of the Indonesian Fertilizer Industry) - Gapura Bhagya, Tombak; Maulidya, Rahmi; Moengin, Parwadi; Cahyati, Sally (Spektrum Industri, 2026)
Indonesia’s archipelagic geography and uneven infrastructure pose persistent challenges to the distribution of subsidized fertilizer, a strategic commodity critical to national food security. While Vehicle Routing Problem (VRP) models are widely applied to improve logistical efficiency, existing studies predominantly focus on algorithmic optimization and pay limited attention to policy constraints, stakeholder complexity, and service trade-offs in regulated distribution systems. This study addresses this limitation by developing a conceptual VRP framework grounded in Soft Systems Methodology (SSM), positioning fertilizer distribution as a policy-constrained socio-technical system. The research follows Check land’s seven-stage SSM process, moving from unstructured problem exploration to the identification of feasible and desirable changes. Supporting tools include VOSviewer for literature mapping, Rich Pictures for stakeholder representation, CATWOE for system definition, and Causal Loop Diagrams (CLD) to capture dynamic interdependencies. The analysis of a multi-echelon distribution network demonstrates that inefficiencies arise not merely from routing limitations but from structural misalignment among routing efficiency, service capacity, inventory control, and government subsidy ceilings. A key insight is the inherent trade-off between cost minimization and service responsiveness in subsidized logistics systems. The study contributes theoretically by reframing VRP within systems thinking, methodologically by integrating qualitative structuring with optimization design, and practically by offering a reusable framework for transparent and policy-responsive public logistics management.